How Interlanguage Process of Students L2 During the Pandemic Era? - Mahfuza, Nurul (Proceeding of International Conference on Language Pedagogy (ICOLP), 2021)
During the COVID-19 pandemic, all activities are carried out virtually and the learning process is included in the effort to learn the target language (IL) in the Interlanguge process. The purpose of this article is to identify what applications students use in their respective L2 processes in the interlanguage process. To collect data in this study, researchers used interviews. Data collection was carried out by interviewing with the help of an interview guide conducted with 6 students of SMK Amal Ikhlas Kampar. The results of this study indicate that students use the Youtube application to achieve the target language mastery level in the inter-language process.